2016
DOI: 10.1016/j.jri.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and estradiol exert an inhibitory effect on the production of anti-inflammatory cytokine IL-10 by activated MZ B cells

Abstract: Please cite this article as: Bommer, I., Muzzio, D.O., Zygmunt, M., Jensen, F., ଝProgesterone and estradiol exert an inhibitory effect on the production of antiinflammatory cytokine IL-10 by activated MZ B cells.Journal of Reproductive Immunology http://dx.doi.org/10. 1016/j.jri.2016.05.008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…B cells were first observed in the placental bed of women early in gestation, which was confirmed by later studies . During early pregnancy, B cells are implicated in the mechanisms of maternal‐fetal tolerance . Decidual B cells modestly increase between 27 and 33 weeks of gestation followed by a slight decline at term .…”
Section: Introductionmentioning
confidence: 60%
“…B cells were first observed in the placental bed of women early in gestation, which was confirmed by later studies . During early pregnancy, B cells are implicated in the mechanisms of maternal‐fetal tolerance . Decidual B cells modestly increase between 27 and 33 weeks of gestation followed by a slight decline at term .…”
Section: Introductionmentioning
confidence: 60%
“…B cells can also be recruited by the chorioamniotic membranes [14] and constitute a portion of the choriodecidual leukocytes [16,57,58]. The role of B cells during pregnancy and its complications have been widely studied by Jensen and collaborators [59][60][61][62][63][64][65][66][67][68]. Taken together, these data provide further evidence that the adaptive limb of immunity is involved in the process of labor.…”
Section: Resultsmentioning
confidence: 82%
“…Interaction of these inflammatory factors exacerbate inflammatory response, leading to the recruitment and infiltration of leukocytes in the liver and thereby aggravating microcirculation disorders [ 21 , 22 ]. Many studies have shown that up-regulation of TNF-α, IL-1β, and IL-6 could directly lead to organ damage by aggravating inflammatory response, and IL-10 could exert an inhibitory effect on inflammation [ 23 , 24 ]. Our results further confirmed these previous studies that significantly declined serum TNF-α, IL-1β, and IL-6 levels was occurred and serum IL-10 level was increased in hepatic ischemia–reperfusion rats by sevoflurane pre-conditioning, which effectively relieved hepatic ischemia–reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%